A map of Europe according to the number of people living abroad (indy100, 2017)
Statistics and headlines about immigration tend to focus on the number of migrants in a country – but another interesting way to look at the topic is levels of emigration from a country. Jakub Marian has published a map according to the number of people born in a country who live abroad, as a percentage of the current population. Here's the map: